The Role of Financial Performance as a Mediator Between Good Corporate Governance and Firm Value - Siti Aisyah (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study examines and analyzes the effect of good corporate governance on the value of banking companies with financial performance as an intervening variable listed on the Indonesia Stock Exchange. The population in this study is the entire banking industry listed on the Indonesia Stock Exchange. The sampling technique used was the purposive sampling technique, namely the determination of the sample based on specific criteria. Based on the established standards, the number of samples obtained is 11 companies. The source of this research data is secondary data, in the form of annual reports of companies and good corporate governance (GCG) for the period 2018–202044444, which were obtained through the official websites of the Indonesia Stock Exchange (IDX) and the official websites of the various companies that were the research sample. The data collection technique is done by documentation. The data obtained will be analyzed by descriptive statistical analysis and using the Partial Least Square (PLS) approach. The results showed that good corporate governance negatively and significantly affects firm value. Meanwhile, good corporate governance positively and substantially affects financial performance. Meanwhile, economic performance has a positive and significant effect on firm value; good corporate governance has a positive and significant effect on firm value through financial performance